The Models of Engaged Learning and Teaching (MELT): Connecting Sophisticated Thinking from Early Childhood to PhD - Fryer, Deidra (Journal of Interdisciplinary Studies in Education, 2022)
The Review provides an overview of the book The Models of Engaged Learning and Teaching (MELT): Connecting Sophisticated Thinking from Early Childhood to PhD. It provides the details about the book and the audience that would find the book useful.